CLERODENDRON INERME PROTECTS CELLULAR INTEGRITY DURING 7,12-DIMETHYLBENZ[A]-ANTHRACENE INDUCED HAMSTER BUCCAL POUCH CARCINOGENESIS - Manoharan, Shanmugam; Kavitha, Kannan; Balakrishnan, Subramanian; Rajalingam, Kasinathan (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
Aim of the present study was to investigate the protective effect of Clerodendron inerme on cellular integrity by measuring the status of glycoconjugates, lipids, osmotic fragility, and membrane bound enzyme activity in 7, 12-dimethylbenz (a) anthracene (DMBA)-induced oral carcinogenesis. Oral squamous cell carcinoma was induced in the buccal pouch of Syrian golden hamsters by painting with 0.5% DMBA in liquid paraffin thrice a week for 14 weeks. The levels of glycoconjugates, lipids, osmotic fragility and membrane bound enzyme activity were analyzed by using specific colorimetric methods. We observed 100% tumor formation in DMBA painted hamsters. Altered glycoconjugates and lipid pattern were observed in DMBA painted hamsters as compared to control hamsters. Erythrocytes from DMBA painted hamsters were more fragile than those from control hamsters. The activity of membrane bound enzyme (Na+ K+ ATPase) decreased in DMBA painted hamsters as compared to control hamsters. Oral administration of aqueous leaf extract of Clerodendron inerme (CiALet) at a dose of 500mg/kg body weight significantly prevented the tumor formation and histopathological abnormalities as well as normalized the above said biochemical variables in DMBA painted hamsters. Our results thus demonstrate the protective effect of Clerodendron inerme on cellular integrity during DMBA induced oral carcinogenesis.